Aluminising of steel with a cathodic arc plasma based method. (4th May 2019) - Çelikel, T.; Kacar, E.; Ürgen, M.
ABSTRACT: Steel samples have been aluminised by cathodic arc PVD using Al cathodes and AC bias. The effect of time and temperature on the growth behaviour of iron aluminide phases under the constant flux of Al vapour was investigated. For samples processed at 1000°C for 30 min a layered structure that consisted of FeAl, followed by dual phase regions of metastable Fe3 Al + FeAl and stable Fe3 Al + α-Fe was observed. Increase of processing time resulted in the formation of Fe2 Al5 . The increase of processing temperature to 1100°C extended the diffusion zone and increased the time for formation of Fe2 Al5 . After 90 min processing at 1000°C and 1100°C the presence of Fe4 Al13 in the Fe2 Al5 phase was determined. It has been observed that the metastable dual phase structures composed of Fe3 Al and FeAl can be transformed into stable Fe3 Al by heat treatment at 500°C.